(untitled) (Journal of the College of Education for Women, 2018)
Metadiscourse markers are means for organizing a writer’s information and create a connection with her/his readers. When students write, they usually focus on one type of these markers that is the interactive markers and belittling the use of the other type which is the interactional markers. That is to say, they emphasize on presenting and organizing their information only. Therefore, this study is conducted to bridge this gap. The researchers have selected 18 thesis abstracts. Nine of them are written by Iraqi students of English and the rest by American students. The aims of the study are to examine the types and sub-types of metadiscourse markers used by American and Iraqi students; investigate comparatively the impact of the metadiscourse markers used in organizing the given information and engaging the readers. To accomplish these aims, Hyland’s model (2005) is adopted. The results show that both Iraqi and American students use the interactive markers more than the interactional ones and the American use of the interactional markers is higher than Iraqi students.